2019
DOI: 10.5380/ce.v24i0.64266
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade De Vida De Pessoas Afetadas Pela Hanseníase Inseridas Em Grupos De Apoio Ao Autocuidado

Abstract: Objetivo: analisar a qualidade de vida de pessoas afetadas pela hanseníase inseridas em grupos deapoio ao autocuidado.Método: estudo quantitativo, descritivo, com 43 participantes em unidades de referência quepossuíam grupos de apoio ao autocuidado em hanseníase, em Recife e Região Metropolitana. Acoleta de dados ocorreu entre janeiro e julho de 2018 com a aplicação do instrumento de avaliaçãode qualidade de vida WHOQOL-bref. A distribuição das variáveis numéricas contínuas foi analisadapelo teste de Kolmogoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
3
0
4
Order By: Relevance
“…(18) A study carried out with patients from leprosy self-care support groups in the city of Recife (PE) and its metropolitan region found lower QoL scores for the environment and physical domains, both with the same mean. (19) However, previous studies observed the physical domain showed the lowest mean QoL scores in populations of individuals with leprosy. (16,20) Despite the fact the WHOQOL-BREF allows comparing its results among different populations, one must take into consideration the notion of QoL suffers personal influences related to the individual's ability to deal with certain situations.…”
Section: ❚ Discussionmentioning
confidence: 93%
“…(18) A study carried out with patients from leprosy self-care support groups in the city of Recife (PE) and its metropolitan region found lower QoL scores for the environment and physical domains, both with the same mean. (19) However, previous studies observed the physical domain showed the lowest mean QoL scores in populations of individuals with leprosy. (16,20) Despite the fact the WHOQOL-BREF allows comparing its results among different populations, one must take into consideration the notion of QoL suffers personal influences related to the individual's ability to deal with certain situations.…”
Section: ❚ Discussionmentioning
confidence: 93%
“…Acerca da faixa etária e do status de trabalho, estudos sobre a situação epidemiológica da hanseníase relataram que as pessoas afetadas pela doença estão na faixa etária economicamente ativa (12,(15)(16) . Pesquisas realizadas em Alagoas (23,7%) e no Pará (57,6%) corroboram a caracterização socioeconômica encontrada neste estudo (14)(15) .…”
Section: Discussionunclassified
“…Apesar do contexto histórico de discriminação, estigma, isolamento e falta de informação, em que as pessoas afetadas pela doença tendem a ser excluídas e desabilitadas de suas relações sociais e de suas atividades econômicas (7)(8) , os participantes não perceberam dificuldades no domínio das Relações Interpessoais. Fazer parte de um grupo de apoio ao autocuidado, espaço de compartilhamento de experiências e dificuldades, pode influenciar a percepção deles em relação a amizades e ao relacionamento entre pessoas que apresentam os mesmos desafios (16) .…”
Section: Discussionunclassified
“…Leprosy compromises mainly the physical component of QoL (2,(6)(7)10,(15)(16)(17)(18)(19)(20)(22)(23)34,44,(48)(49)52,(56)(57)(58)(60)(61)(63)(64)(65)84) .…”
Section: Main Findingsmentioning
confidence: 99%